Pengaruh Penggunaan Media Pembelajaran E-Learning Terhadap Motivasi Mahasiswa - Andy Hakim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Learning is a two-way activity carried out by teaching staff and students carried out in a learning environment. Learning that is carried out online at universities is assisted by a media or it can also be called learning media. Learning motivation is a psychological driving force from within a person to be able to carry out learning activities and increase skill experience. The purpose of the study was to see whether online learning and the use of learning media had an influence on students' learning motivation. Where in this study using quantitative research methods by testing using SPSS. The results in the H0 study were rejected, which means that online learning has no effect on research motivation. H1 is accepted where online learning media has an influencing role on motivation for students. And overall the variables have a stimulant effect on student motivation with the acceptance of H3 research